Altered ripple density inside seizure onset zone in patients with focal cortical dysplasia‐associated epilepsy. Issue 6 (7th May 2021) - Xu, Cuiping; Zhang, Xiaohua; Zhang, Guojun; Yan, Xiaoming; Ma, Kai; Qiao, Liang; Wang, Xueyuan; Zhang, Xi; Yu, Tao; Wang, Yuping; Li, Yongjie
Abstract: Purpose: To evaluate the clinical and stereoelectroencephalography (SEEG) features and postsurgical outcome in a uniform series of patients who underwent epilepsy surgery and had pathologically confirmation of focal cortical dysplasia (FCD). Methods: We studied consecutive patients with drug‐refractory epilepsy who underwent SEEG recording. The high‐frequency oscillations (HFOs) features of SEEG, clinical characteristics, and surgical outcome were evaluated. Results: Sixty patients (31 FCD type I, 13 II, and 16 III) were analyzed retrospectively. Patients with type II tended to have their seizures at an earlier age than those with I and III ( p  < .01). Six different ictal onset patterns (IOPs) were identified. In patients with temporal lobe epilepsy (TLE), the most common patterns were rhythmic spikes or spike waves and LFRS, and in patients with extratemporal epilepsy, the most common patterns were low‐voltage fast activity (LVFA) and rhythmic spikes or spike waves. In addition, ripple density was found to increase significantly from the interictal to ictal onset sections and from the ictal onset to ictal evolution sections in patients with FCD I ( p  < .001). Regarding the distinct IOPs, ripple density continued to increase significantly between the interictal and ictal onset sections in LVFA, rhythmic spikes or spike waves, and burst of high‐amplitude polyspikes ( p  < .05). Ripple density decreased between ictal onset and ictal evolution sections in patterns of LVFA and rhythmic spikes or spike waves ( p  < .05). The mean follow‐up duration was 2.7 years (range 1–4.2), and 66.7% ( n  = 40) were class I. Patients with subtypes III and II had favorable surgical outcome than those with I. Conclusion: The clinical expression of seizure may depend on the pathological types with FCD II patients exhibiting their seizures at an earlier age. Distinct IOPs may demonstrate different ripple features and distinguishing the IOPs is very necessary to have an insight into the electrophysiological characteristics. Abstract : Distinct IOPs demonstrate different ripples features. The clinical expression of seizure depend on the pathological types with FCD II patients exhibiting their seizures at an earlier age.